Design of hybrid solar and pyco hydro power plant using water reservoir tank - Muttaqin, Asyrofi; Syukriyadin, Syukriyadin; Syahrizal, Syahrizal; Alfisyahrin, Alfisyahrin; Helta, Fahri (Geuthèë Institute, 2024)
The energy contained in the flow of water from the tank can be utilized as an additional source of electrical energy, namely by making a Pico Hydro Power Plant (PLTPh). However, the flow of water produced is certainly not strong enough because it only relies on the height of the tank laying, and the water discharge is not too large. So, the energy from sunlight is also utilized simultaneously and becomes a hybrid PV-hydro power plant (PLTH PV-hydro) with the aim of producing more optimal alternative energy. PLTH PV-Hydro is designed using a combination of 10 WP monocrystalline solar panels and two 10W DC generators coupled with turbines. The distance between the water drop point and the generator is designed to be as high as 2 meters and uses a 12 V, 5Ah VRLA battery as an electrical energy storage system. Based on the tests that have been carried out, the water discharge measurement results are 147.82 cm3/s = 147.82 × 10-3 l/s. The total power that PLTH can generate is 5.32 Watts using a 5-watt lamp load, and it can charge the battery within 6 hours.